A cognitive perspective on equivalent effect: using eye tracking to measure equivalence in source text and target text cognitive effects on readers. (2nd January 2019) - Walker, Callum
ABSTRACT: Eye-tracking methods have long been used to explore cognitive processing in reading, but the recent burgeoning of such methods in the field of translation studies has focused almost entirely on the translation process or audiovisual translation, neglecting the effects of the translation product itself. This paper presents a proof-of-concept study using eye tracking to compare fixation data between native readers of a French literary source text and native readers of its English translation at specific, corresponding points in the texts. The preliminary data are consistent with previous findings on the relationship between the features of the fixated word and fixation durations. These findings are also consistent with stylistic analyses and indicate that this method can be used to compare the levels of cognitive effort between two readership groups in order to investigate whether their experience is similar – whether an 'equivalent effect' has been achieved – thus contributing to the ongoing discourse surrounding equivalence in translation studies.